Inborn differences in emotional behavior coincide with alterations in hypothalamic paraventricular motor projections. (15th December 2020) - Shupe, Elizabeth A.; Glover, Matthew E.; Unroe, Keaton A.; Kerman, Ilan A.; Clinton, Sarah M.
Abstract: Integrated behavioral responses to emotionally salient stimuli require the concomitant activation of descending neural circuits that integrate physiological, affective, and motor responses to stress. Our previous work interrogated descending circuits in the brainstem and spinal cord that project to motor and sympathetic targets. The hypothalamic paraventricular nucleus (PVN), a key node of this circuitry, integrates multiple motor and sympathetic responses activated by stress. The present study sought to determine whether descending projections from the PVN to targets in muscle and adrenal gland are differentially organized in rats with inborn differences in emotionality and stress responsivity. We utilized retrograde transsynaptic tract‐tracing with unique pseudorabies virus (PRV) recombinants that were injected into sympathectomized gastrocnemius muscle and adrenal gland in two rat models featuring inborn differences in emotional behavior. Our tract‐tracing results revealed a significant decrease in the number of PVN neurons with poly‐synaptic projections to the gastrocnemius in male Wistar Kyoto [WKY] rats (versus Sprague Dawley rats) and selectively bred Low Novelty Responder [bLR] rats (versus selectively bred High Novelty Responder [bHR] rats). These neuroanatomical differences mirrored behavioral observations showing that both WKY and bLR rats display marked inhibition of emotional motor responses in a variety of settings relative to their respective controls. Our findings suggest that, in male rodents, PVN poly‐synaptic projections to skeletal muscle may regulate emotional motor and coping responses to stress. More broadly, perturbations in PVN motor circuitry may play a role in mediating psychomotor disturbances observed in depression or anxiety‐related disorders. Abstract : Retrograde transsynaptic tract‐tracing with pseudorabies virus (PRV) recombinants injected into muscle and adrenal gland was used to interrogate premotor and presympathetic projections from the hypothalamic paraventricular nucleus (PVN) in two rat models with inborn differences in emotionality. Wistar Kyoto (WKY) and selectively bred Low Novelty Responder (bLR) rats have reduced PVN premotor connections to skeletal muscle relative to outbred Sprague Dawley (SD) and selectively bred High Novelty Responder (bHR) rats, respectively. PVN projections to muscle may regulate emotional motor responses in rodents.